FN1 shapes the behavior of papillary thyroid carcinoma through alternative splicing of EDB region - Mian Liu; Pei Chen; Bo Wei; Hai-Long Tan; Ya-Xin Zhao; Lei Ai; Ning Li; Ying-Ke Jiang; Jing Lin; Shi-Jin Li; Shi Chang (Scientific Reports)
Abstract Papillary thyroid cancer (PTC) is often characterized by indolent behavior, small tumors with slow cell proliferation and a tendency to metastasize to cervical lymph node simultaneously, and the molecular mechanisms underlying that remain poorly understood. In this study, FN1 was the hottest gene of PTC and distinctive expression in PTC cells. FN1 deficiency severely inhibited the p53 signaling pathway, especially cyclin proteins, resulting in increased cell growth but hampered invasion. The alternatively splicing EDB region of FN1 was exclusively expressed in tumors, which impacted integrin β1 (ITGB1) bonding FN1 and its secretion process, resulting in completely distinct roles of two isoforms that FN1 including and skipping EDB domain. The isoform EDB(–)FN1 intracellularly inhibited tumor proliferation by upregulating p21 expression, whereas extracellular EDB(+)FN1 promoted lymph node metastasis via the VEGF signaling pathway in vitro and in vivo. Moreover, the alternative splicing EDB region of FN1 was modulated by p53-targeted protein ZMAT3 which activated cell migration and lymphoangiogenesis. Collectively, combined with p53-induced proteins, FN1 played both anti- and pro-cancer roles owing to EDB domain alternative splicing. FN1 is a potential determinant behind the characteristic behavior of PTC, which may contribute to a deeper understanding of the peculiarity of PTC and provide a promising target for regional lymph node metastasis.